IMPLEMENTASI PENDIDIKAN AQIDAH AKHLAK MENURUT PRESPEKTIF IMAM AL-GHAZALI DALAM MENCARI ILMU AGAMA - Riansyah Atmana Ruhuputty; Ibnu Jazari; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Education is a foundation for advancing civilization, and can develop society so that later it will be able to make generations work for their interests, if a nation is in shock or progress is hampered, then the first thing to review is its education system. Seeing the quality and condition of this millennial era, the problems faced in the world of education, especially and almost a lot of people agree with, are Islamic education which is the main guideline for moral formation. Most of the people in society today still believe that Islamic religious education is very capable of directing life to a good goal. This research is a library research (library research) using a non-interactive approach or what is commonly referred to as an analytical researcher. This is non-interactive research, researchers collect, identify, analyze, and synthesize data, to then interpret concepts, policies and events that are directly or indirectly observed. Research has a descriptive analysis, which is a method that describes and describes systematically. The results of this study indicate that Imam Al-Ghazali is a high priest with a very high enthusiasm for knowledge. This can be proven by the works of his book essays. Moral education is an effort made consciously to guide and change habits, to achieve noble morals, while the goal of moral education according to Imam Al-Ghozali is to form humans who can get closer to Allah SWT. So that it can give happiness both in this world and in the hereafter. The theory of Imam Al-Ghozali Moral education with the theory of Perennialism and Positivism in the book Ihya 'Ulumuddin has a relationship to the context of ideas. Although in the context the actualization is different because of several factors that grow along with the times.